THE INFLUENCE OF SERVICE QUALITY DIMENSION TOWARDS CUSTOMER SATISFACTION AT PT. ENERTIKA DWIPA CIPTA (PULOMAS GOLF COURSE) JAKARTA - Laksmi, Ni Made Dewi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study indentifies the influence of service quality dimension toward customer satisfaction at PT. Enertika Dwipa Cipta (Pulomas Golf Course), Jakarta. InÂ service quality dimension, there are five variables, as follows: tangibility, reliability, responsiveness, assurance, and empathy. This study uses explanatory approach, as the research method. The data were collected by employing interview, observation, internet browsing, and questionnaire. The sampling technique used in this study is probability sampling and there are 60 respondents. The conclusion of this study is that the variable of service quality dimension simultaneously and partially has significant influence toward customer satisfaction at PT. Enertika Dwipa Cipta (Pulomas Golf Course), Jakarta. Based on the calculation of multiple linear regression, it is known that the responsiveness variable have the dominant influence toward the customer satisfaction at di PT. Enertika Dwipa Cipta (Pulomas Golf Course), Jakarta Key Words: Service Quality, Customer Satisfaction, Service Quality Dimension.